2021
DOI: 10.3389/fmars.2021.690991
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Microplastic in Fish From Australia and Fiji

Abstract: Awareness surrounding plastic pollution has increased significantly in the past decade, leading to concerns on potential adverse effects on biota, including the consumption of microplastic by fish. Globally, plastic has been found in many species of fish, but little research has been undertaken in the southern hemisphere. We assessed the abundance and type of plastic in fish captured and sold for human consumption in Australia and Fiji. Fish (goatfish, sea mullet, paddletail, and common coral trout) had their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 75 publications
1
15
2
Order By: Relevance
“…A Singapore study that analyzed microplastics in commercial shrimp reported an average of 13.4–7050 items, and another study that sampled shrimp in the Arabian sea reported a microplastic average of 1220 items. , For studies carried out on mussels, researchers found an average of 1.53 items/g in green mussels sold in Thailand, an average of 0.9–4.6 items/g in mussels found on the coastlines in China, and an average of 1.4 items/g of supermarket-bought mussels in the United Kingdom. Another study compared the amount of microplastic in fish sold for human consumption. Fish from Fiji had 0.86 pieces/fish, almost two times lower than the average of 1.58 pieces per fish reported in an Australian study . These studies show that microplastics are pervasive even in seafood.…”
Section: Introductioncontrasting
confidence: 58%
See 1 more Smart Citation
“…A Singapore study that analyzed microplastics in commercial shrimp reported an average of 13.4–7050 items, and another study that sampled shrimp in the Arabian sea reported a microplastic average of 1220 items. , For studies carried out on mussels, researchers found an average of 1.53 items/g in green mussels sold in Thailand, an average of 0.9–4.6 items/g in mussels found on the coastlines in China, and an average of 1.4 items/g of supermarket-bought mussels in the United Kingdom. Another study compared the amount of microplastic in fish sold for human consumption. Fish from Fiji had 0.86 pieces/fish, almost two times lower than the average of 1.58 pieces per fish reported in an Australian study . These studies show that microplastics are pervasive even in seafood.…”
Section: Introductioncontrasting
confidence: 58%
“…Fish from Fiji had 0.86 pieces/fish, almost two times lower than the average of 1.58 pieces per fish reported in an Australian study. 44 These studies show that microplastics are pervasive even in seafood. Thus, human consumption of microplastics via seafood is likely.…”
Section: Introductionmentioning
confidence: 94%
“…Microplastic contamination in ecological risk is the adverse environmental effects of exposure. Marine organisms are exposed through direct and indirect ingestion of MP or inhalation (Hidalgo Ruz, et al, 2012;Kaposi et al, 2013;Neves et al, 2015;Ogunola and Palanisami, 2016;Auta et al, 2017;Gallo et al, 2018;Wibowo et al, 2019;Ugwu et al, 2021;Wootton et al, 2021;Harqu and Fan, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…As bleaching processes happen in the marine ecosystem, it is difficult to comment on MPs' color (Stolte et al, 2015). Nevertheless, the color of the MPs is a significant factor as the marine organisms prey on colored MPs for resembling their prey, and the results have already been documented in many parts of the world (Ory et al, 2018;Botterell et al, 2019;Hossain et al, 2019Hossain et al, , 2020Hoellein et al, 2021;Liu et al, 2021;Muller, 2021;Wootton et al, 2021).…”
Section: Characteristics Of Microplasticsmentioning
confidence: 99%